Association between intelligence and type-specific stroke: a population-based cohort study of early fatal and non-fatal stroke in one million Swedish men. Issue 10 (14th October 2009) - Modig Wennerstad, Karin; Silventoinen, Karri; Tynelius, Per; Bergman, Lars; Rasmussen, Finn
Abstract : Background: Inverse associations between IQ and stroke have been reported in a few studies, but none have investigated subtypes of stroke, nor have they studied fatal and non-fatal stroke separately. Stroke is a heterogenic disease and strength of associations with IQ and putative causal pathways cannot be assumed to be identical for different subtypes. Methods: IQ was measured for 1.1 million Swedish men, born 1951 to 1976. Data from several national registers were linked and the cohort followed until the end of 2006 for non-fatal, and 2004 for fatal stroke. HRs with 95% CIs adjusted for age, body mass index, blood pressure and socioeconomic factors were estimated using Cox proportional hazards models. Results: Inverse associations were found between IQ and all stroke subtypes. The strength of the associations differed by subtype, with the strongest RR found for haemorrhagic stroke. In adjusted models using IQ as a continuous variable over a standard nine point scale, HR for mortality in all stroke was 0.89 (95% CI 0.85 to 0.93), that is an 11% decrease in stroke risk per unit increase in IQ. For non-fatal stroke, the corresponding HR was 0.92 (95% CI 0.91 to 0.93). The results were based on a rather young cohort, and results should therefore be generalised to early stroke events rather than the general population. Conclusions: Inverse associations were found between IQ and all stroke subtypes, fatal and non-fatal. For all types of non-fatal stroke, the inverse associations with IQ remained after adjustments for childhood and adult socioeconomic position.